Evaluation of confirmatory data following the Article 12 MRL review for teflubenzuron. (15th October 2018) - ; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: The applicant BASF Agro BV submitted a request to the competent national authority in United Kingdom to evaluate the confirmatory data that were identified for teflubenzuron in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new metabolism study on leafy crops, a study investigating the nature of residues under standard hydrolytic conditions and a validated analytical method to determine residues of teflubenzuron in products of animal origin were submitted. The data gaps were considered satisfactorily addressed. The new information provided does not require a revision of risk assessment performed for teflubenzuron.